The Effect of Minimally Invasive Surgical Repair on the Lung Volumes of Patients with Pectus Excavatum - Sengul, Aysen Taslak; Sahin, Bunyamin; Celenk, Cetin; Basoglu, Ahmet; Sengul, Bilal (The Thoracic and Cardiovascular Surgeon, 2014)
Objectives To assess the increase in lung volume after Nuss surgery in patients with pectus excavatum (PE) by using stereological methods and to evaluate the correlation between the lung volume and spirometry findings.Methods Twenty patients, treated for PE between 2008 and 2010, were evaluated prospectively. They underwent preoperative chest radiography, computed thorax tomography (CTT), and spirometry. Thereafter, the Haller index was calculated for each patient. In the third postoperative month, CTT and spirometry were repeated.Lung volumes and volume fractions were evaluated using CTT images, applying the Cavalieri principle for stereological methods. Then the correlation between the pre- and postoperative values of the lung volumes with spirometry findings was determined.Results Volumes of the right and left lungs were calculated stereologically, using CTT images. Postoperative volume increase of ∼417.6 ± 747.6 mL was detected. The maximum volume increase was observed in the left lung. In the postoperative period, the total volume increase and the volume increase detected in the left lung were found to be statistically significant (p < 0.05).The preoperative correlation coefficients (r) for forced vital capacity, forced expiratory volume in 1 second, and forced expiratory flow 25 to 75% were 0.67, 0.68, and 0.61, respectively; the postoperative r figures were 0.43, 0.42, and 0.35, respectively. Although there was a strong correlation between the preoperative lung volume and spirometry findings (p < 0.05), no correlation was observed between the postoperative lung volume and spirometry findings (p > 0.05).Conclusions Postoperative pulmonary volume increase occurs in patients with PE after Nuss surgery. However, postoperative spirometry findings may not reflect morphological improvement because pain restricts thoracic movements. Therefore, in patients with PE, quantitative evaluation of the results of surgical repair is possible using the CTT images through a combination of stereological methods.
Keywords: pectus excavatum; stereological method; spirometry